SATISFACTION WITH NURSING CARE OF ONCOLOGY PATIENTS ON OUTPATIENT ANTINEOPLASTIC DRUGS - Ferreira, Jean Vitor Silva; Bandeira, Gabriel de Luca Sousa; Sagica, Tais dos Passos; Conceição, Crislen de Melo; Souza, Nathalia Oliveira de; Costa, Marta Solange Camarinha Ramos; Ramos, Aline Maria Pereira Cruz (Cogitare Enfermagem, 2023)
Objective: Evaluate the satisfaction of outpatient oncology users taking antineoplastic drugs about nursing care. Methods: Exsectional study with a quantitative approach, carried out at the Chemotherapy Service of a university hospital located in Belém-PA – Brazil, with 200 users, from June 2019 to June 2022, through interviews and use of the Patient Satisfaction Instrument. Chi-square analysis, Pearson p-value, and chi-square analysis were applied, and the p-value ≤ 0.05 was considered. Results: Users reported good satisfaction in the overall average of the domains (>90%), highlighting the technical-professional domain, followed by the educational and confidence domains. The variables of clarification of medical guidelines, giving good advice, and taking the initiative after patient responses were associated with user satisfaction according to cancer topography and staff availability to those with different degrees of staging. Conclusion: This study assists managers in identifying and planning improvements in areas and services.